Peran Kepemimpinan Transformasional dalam Meningkatkan Motivasi Kerja dan Kinerja Pegawai - Fitriani, Adinda; Muafi (SAFE-Network, 2023)
This study aims to determine how the form of transformational leadership style is applied in the Bappelitbangda office of Batu Bara Regency and how the influence of the role of this leadership style in increasing work motivation and employee performance then comparing the situation in the field with the theories that have been obtained by the author. The data analysis method used by the author in this research is a case study with a qualitative method and descriptive approach obtained through observation and interview data collection techniques with the employees concerned as primary data, as well as conducting documentation in the environment around the office as secondary data. The results of the research that has been done show that the role of transformational leadership applied by the leader has been running well, there is a positive influence in increasing work motivation and employee performance and can be said to be able to increase work motivation and employee performance at the Bappelitbangda office, Batu Bara Regency, North Sumatra.